The role of “Market Day” in developing entrepreneurial habitus at MTS Zia Salsabila School - Dean Antania Simatupang; Sakti Ritonga (Curricula: Journal of Curriculum Development, 2025)
The development of entrepreneurial spirit in secondary education has become an important focus in preparing adaptive and innovative generations. “Market Day”, as an experience-based learning strategy, has been implemented in various institutions. However, no research has analyzed the formation of students' entrepreneurial habitus through this activity within Pierre Bourdieu's theoretical framework. This research aims to analyze the role of “Market Day” in developing students' entrepreneurial habitus at MTs Zia Salsabila, specifically by identifying the implementation of activities and evaluating its contribution to forming habitus through the internalization of entrepreneurial mindset, attitudes, and habits. The research used a descriptive qualitative approach with a purposive sampling technique involving the principal, two teachers, and five students. Data collection was conducted through semi-structured interviews, participatory observation, and a documentation study, then analyzed using the Miles-Huberman-Saldaña interactive model. “Market Day” successfully developed entrepreneurial habitus through three dimensions: cognitive (ability to manage capital and marketing strategies), affective (independence, self-confidence, risk-taking, courage), and behavioral (honesty, responsibility, cooperation). Students demonstrated a transformation from a job seeker to a job creator mindset. “Market Day” proved effective as an arena for forming permanent entrepreneurial habitus through repeated experiences and systematic internalization of entrepreneurial values.    Abstrak Pengembangan jiwa kewirausahaan dalam pendidikan menengah menjadi fokus penting dalam mempersiapkan generasi yang adaptif dan inovatif. “Market Day” sebagai strategi pembelajaran berbasis pengalaman telah diterapkan di berbagai institusi, namun belum ada penelitian yang menganalisis pembentukan habitus kewirausahaan murid melalui kegiatan ini dalam kerangka teori Pierre Bourdieu. Penelitian ini bertujuan menganalisis peran “Market Day” dalam mengembangkan habitus kewirausahaan murid di MTs Zia Salsabila, khususnya mengidentifikasi implementasi kegiatan dan mengevaluasi kontribusinya dalam membentuk habitus melalui internalisasi pola pikir, sikap, dan kebiasaan wirausaha. Penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik purposive sampling terhadap kepala sekolah, dua guru, dan lima murid. Pengumpulan data dilakukan melalui wawancara semi-terstruktur, observasi partisipatif, dan studi dokumentasi, kemudian dianalisis dengan model interaktif Miles-Huberman-Saldaña. “Market Day” berhasil mengembangkan habitus kewirausahaan melalui tiga dimensi: kognitif (kemampuan mengelola modal dan strategi pemasaran), afektif (kemandirian, kepercayaan diri, keberanian mengambil risiko), dan behavioral (kejujuran, tanggung jawab, kerja sama). Murid menunjukkan transformasi pola pikir dari job seeker menjadi job creator. “Market Day” terbukti efektif sebagai arena pembentukan habitus kewirausahaan yang permanen melalui pengalaman berulang dan internalisasi sistematis nilai-nilai kewirausahaan. Kata Kunci: habitus, kewirausahaan; Market Day; pendidikan karakter; Pierre Bourdieu